Membangun Strategi 'Low Budget High Impact' di Era New Wave Marketing: Kajian atas Perusahaan-Perusahaan Top Brand 2000-2007 - Kodrat, David Sukardi (International Research Journal of Business Studies, 2009)
The purpose of this research is to test a new wave marketing phenomena: low budget, high impact marketing. This research uses enterprises which continuously get Top Brand from 2000 to 2007 as a population. Sampling selection is performed based on purposive sampling with object to gain samples according to the research aim. Based on those criteria, there are 19 companies, which have been fulfilling the conditions required. The result reveals that coefficients determinants (R2) is 0,430. It means that 43 percents of independent variables (log sales, business ratio and net profit margin) with significant influence to Top Brand Index. The influential variable to Top Brand Index is Net Profit Margin with positive direction. In other word, the bigger of company’s net profit margin, the bigger of Top Brand Index. It is proofed that winning Top Brands are the brands apply low budget, high impact as phenomena occurred in new wave marketing.